Distribution of the Endangered American Burying Beetle at the Northwestern Limit of its Range. Issue 1 (22nd January 2018) - Jenkins, Tanner; Hoback, W Wyatt; Leasure, Doug; Mulder, Phillip; Davis, Craig
Abstract: The American burying beetle (ABB), Nicrophorus americanus (Olivier; Coleoptera: Silphidae), historically occurred in the eastern 35 U.S. States from Canada to Texas and is classified as a habitat generalist. The ABB was listed as a federally endangered species in 1989 with remaining distribution in only six U.S. States. Within these states, populations of ABB are disjunct, occurring in mostly undisturbed habitats associated with multiple soil types and vegetation structure. In Nebraska, the distribution of the ABB has been mapped in two ecoregions, the Sandhills and the Loess Canyons. In this project, we developed and compared a logistic regression model and a random forest model of ABB distribution at its northern and eastern edge in the Northern Plains ecoregions of Nebraska and South Dakota. We used baited pitfall sampling for five trap nights at 482 unique sites to establish presence of ABB at 177 sites. Distribution was not uniform in this ecoregion and the random forest model better predicted occurrence in this area. The results show that the ABB population in the northern plains ecoregion is unique from the previous model of the Nebraska Sandhills despite these ecoregions being adjacent. The model results also reduce requirements to survey and conduct habitat mitigation for ABB in approximately 77, 938 hectares of Nebraska and South Dakota that was considered potential habitat while prioritizing areas for conservation.